The cost of opioid use disorder-related conditions in Medicare. (1st March 2023) - Mark, Tami L.; Parish, William J.; Weber, Ellen M.; Steinberg, Deborah G.; Henretty, Kristen
Abstract: Background: Medicare coverage excludes some levels of substance use disorder (SUD) care, such as intensive outpatient and residential treatment. Expanding access to SUD treatment could increase Medicare spending. However, these costs could be offset if SUD treatment resulted in cost savings from reducing SUD-related medical events and SUD-related medical comorbidities. Methods: This study estimated cost savings from expanding access to SUD treatment for persons with opioid use disorders (OUD) using three methods. First, we compared total Medicare fee-for-service spending on individuals with OUD and no treatment with OUD medications (MOUD) to Medicare spending on individuals without OUD after matching on age/sex/Medicare-Medicaid eligibility status. Second, we compared Medicare spending on individuals with OUD who received MOUD to spending individuals with OUD who did not receive MOUD. Third, we determined OUD-attributable Medicare spending for comorbid physical and mental conditions with a strong association with OUD. Results: Beneficiaries with OUD but no MOUD totaled $15.8 billion more than beneficiaries without OUD. Beneficiaries with OUD but no MOUD totaled $12.1 billion more than individuals with OUD and MOUD. Lastly, Medicare spending on OUD-attributable comorbidities was $4.7 billion if all medical and mental health comorbidities were included and $3.0 billion with only medical comorbidities. The totals could be 1.7 times higher if Medicare Advantage enrollees were included. Conclusion: Expanding Medicare coverage of appropriate levels of care could improve access to effective treatment and reduce the costs associated with untreated OUD. This will likely result in substantial Medicare cost savings. Highlights: Medicare beneficiaries with opioid use disorders (OUD) cost Medicare $15.8 billion. OUD attributable comorbidities cost Medicare $4.7 billion. Medicare spending was significantly less in treated than non-treated beneficiaries with OUD.